Evaluation of the Microvascular Research Center Training Program for Assessing Microsurgical Skills in Trainee Surgeons - Komatsu, Seiji (The Korean Society of Plastic and Reconstructive Surgeons, 2013)
BACKGROUND: We established the Microvascular Research Center Training Program (MRCP) to help trainee surgeons acquire and develop microsurgical skills. Medical students were recruited to undergo the MRCP to assess the effectiveness of the MRCP for trainee surgeons. METHODS: Twenty-two medical students with no prior microsurgical experience, who completed the course from 2005 to 2012, were included. The MRCP comprises 5 stages of training, each with specific passing requirements. Stages 1 and 2 involve anastomosing silicone tubes and blood vessels of chicken carcasses, respectively, within 20 minutes. Stage 3 involves anastomosing the femoral artery and vein of live rats with a 1-day patency rate of >80%. Stage 4 requires replantation of free superficial inferior epigastric artery flaps in rats with a 7-day success rate of >80%. Stage 5 involves successful completion of one case of rat replantation/transplantation. We calculated the passing rate for each stage and recorded the number of anastomoses required to pass stages 3 and 4. RESULTS: The passing rates were 100% (22/22) for stages 1 and 2, 86.4% (19/22) for stage 3, 59.1% (13/22) for stage 4, and 55.0% (11/20) for stage 5. The number of anastomoses performed was 17.2±12.2 in stage 3 and 11.3±8.1 in stage 4. CONCLUSIONS: Majority of the medical students who undertook the MRCP acquired basic microsurgical skills. Thus, we conclude that the MRCP is an effective microsurgery training program for trainee surgeons.